2006
DOI: 10.1103/physrevlett.97.235003
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Spontaneous Toroidal Rotation Inversion in Ohmically Heated Tokamak Plasmas

Abstract: Bulk plasma toroidal rotation is observed to invert spontaneously from counter to cocurrent direction in TCV (Tokamak à Configuration Variable) Ohmically heated discharges, in low confinement mode, without momentum input. The inversion occurs in high current discharges, when the plasma electron density exceeds a well-defined threshold. The transition between the two rotational regimes has been studied by means of density ramps. The results provide evidence of a change of the balance of nondiffusive momentum fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
172
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(188 citation statements)
references
References 15 publications
16
172
0
Order By: Relevance
“…It covers a region from well outside the sawtooth inversion radius to just inside the last CXRS measurement points. While the core of TCV L-mode plasmas usually rotates in the countercurrent direction, it can also rotate in the cocurrent direction [19,21,22]. Such a reversed rotation state is, quite interestingly, sometimes observed in the present experiments.…”
supporting
confidence: 58%
“…It covers a region from well outside the sawtooth inversion radius to just inside the last CXRS measurement points. While the core of TCV L-mode plasmas usually rotates in the countercurrent direction, it can also rotate in the cocurrent direction [19,21,22]. Such a reversed rotation state is, quite interestingly, sometimes observed in the present experiments.…”
supporting
confidence: 58%
“…(9) to its sub-class associated with a vanishing mean toroidal velocity therefore allows to relax this degeneracy and unambiguously relate the radial electric field to the poloidal rotation and the thermodynamic forces whilst accurately modeling the exact cross-field transport and flow generation mechanisms in the radial-poloidal plane as a more general Galilean-invariant Fokker-Planck operator would. On the other hand, this sim- [76][77][78] In that case, the Galilean-invariant versions Eqs. (3) and (18) are required; a dedicated study of intrinsic rotation with both GYSELA and XGC1 is to be reported elsewhere.…”
Section: Discussion: Which Physics Can We Address?mentioning
confidence: 99%
“…In terms of its direction and scaling trends, L-mode rotation seems to be a complex phenomenon with various competing effects, which may frequently involve sign flips. 7,9,10 In contrast, H mode rotation is usually in the co-current direction, and the on-axis plasma velocity appears to increase with stored energy W p and decrease with total plasma current I p . 11 This empirical scaling, which has come to be called the Rice scaling, particularly manifests itself strongly in Alcator C-Mod and D-IIID, 1,2 and if taken at face value gives rather optimistic predictions for ITER's rotation speed.…”
Section: Introductionmentioning
confidence: 99%